Little Girl: The Weaponization of Infantilized and Roboticized (Hyper)Femininity in Postwar Japanese Popular Culture - Azzi, Amanda (Université d'Ottawa | University of Ottawa, 2021)
Atomic bombs Little Boy and Fat Man left postwar Japan in deep trauma and loss of national identity. The nation’s ultimate way of compensation for its defeat in World War II led to a redefinition of Japanese self-realization from a “masculine” state to a “feminine” one. This research paper explores the ways in which Japanese artists and creators interpreted what they saw as the nation-state’s ‘castration’ and shift to a ‘little boy’. Postwar Japan consequently embraces kawaii culture to compensate for its lost status through soft power with the development and transnational influence of its animanga along with its new fashion and toy industry. My focus on the manga Sailor Moon, the anime Violet Evergarden, the Lolita fashion aesthetic and finally the Sanio Co. toy Hello Kitty demonstrates this embracing of kawaii culture and its infantilizing and roboticizing hyperfemininity, which, I argue, allows for the overcoming of American hegemony and the embracing of a new transnational soft power for Japan.
Keywords: postwar Japan; kawaii; American hegemony; roboticization; infantilized femininity